The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/ijc.10100
|View full text |Cite
|
Sign up to set email alerts
|

Dominant‐negative inhibition of breast cancer resistance protein as drug efflux pump through the inhibition of S‐S dependent homodimerization

Abstract: Key words: drug resistance; ABC transporter; mitoxantrone; retrovirus vector Tumor cells that acquire resistance to certain chemotherapeutic agents sometimes develop cross-resistance to other structurally unrelated drugs. 1 This phenomenon is known as multi-drug resistance. A family of ATP-binding cassette (ABC) transporters such as MDR1 gene product P-glycoprotein 1-4 and MRP1 5 is involved in multidrug resistance. They pump out various structurally unrelated antitumor agents in an energy-dependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
184
2
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(211 citation statements)
references
References 17 publications
(13 reference statements)
17
184
2
5
Order By: Relevance
“…In the cross-linking experiments presented in this manuscript ( Figure 5 and Figure 9/B) a stronger signal was observed on immunoblot in the samples treated with the cross-linking agents compared to the non-treated ones. This phenomenon has not been explained, although, it has been reported by other investigators and in our previous studies as well (21) (33) As the lower protein expression levels seen on immunoblot and the lack of surface expression might be the result of abnormal folding and/or dimerization, using the baculovirus heterologous expression system, we expressed the G553L mutant in Sf9 insect cells (Spodoptera frugiperda ovarian cells), which might be more tolerant of an aberrant protein and typically yields higher levels of protein expression (34). Interestingly, we found that the G553L mutant migrates to the cell surface in the insect cells as demonstrated by flow cytometry with the 5D3 antibody ( Figure 6A).…”
Section: Resultscontrasting
confidence: 48%
“…In the cross-linking experiments presented in this manuscript ( Figure 5 and Figure 9/B) a stronger signal was observed on immunoblot in the samples treated with the cross-linking agents compared to the non-treated ones. This phenomenon has not been explained, although, it has been reported by other investigators and in our previous studies as well (21) (33) As the lower protein expression levels seen on immunoblot and the lack of surface expression might be the result of abnormal folding and/or dimerization, using the baculovirus heterologous expression system, we expressed the G553L mutant in Sf9 insect cells (Spodoptera frugiperda ovarian cells), which might be more tolerant of an aberrant protein and typically yields higher levels of protein expression (34). Interestingly, we found that the G553L mutant migrates to the cell surface in the insect cells as demonstrated by flow cytometry with the 5D3 antibody ( Figure 6A).…”
Section: Resultscontrasting
confidence: 48%
“…SN-38-resistant cells were cloned using the limiting dilution technique, and one well-growing clone, A549/SN4, was selected for further experiments. HCT116/BCRP and P388/BCRP cells were established by the transduction of HCT116 and P388 cells, respectively, with the HaBCRP retrovirus, a Ha retrovirus carrying Myc-tagged human BCRP cDNA (25). K562/ MDR cells were established by the transduction of K562 cells with the HaMDR retrovirus, a Ha retrovirus containing human MDR1 cDNA (26).…”
Section: Cells and Cell Culturesmentioning
confidence: 99%
“…BCRP transport function can be inhibited by dominant-negative BCRP mutants, strongly suggesting that homodimer formation is essential for BCRP function (Kage et al, 2002). BCRP mutants, generated by PCR mutagenesis, were transfected into PA317 cells and tested for the loss of BCRP function.…”
Section: Gene Therapy Approaches To Modulating Bcrpmentioning
confidence: 99%